Clinical Outcome of Posterior Fossa Tumor Surgery Without Preoperative Ventriculo-peritoneal Shunt - Islam, MR; Islam, KMT; Hossain, M; Rashid, MH; Dhakhal, S; Khair, A; Barua, KK; Hossain, MA (Bangladesh Medical Journal, 2012)
The aim of the study was to assess the clinical outcome of surgically treated patients with posterior fossa tumor with hydrocephalus with symptoms and sings of raised intracranial pressure without pre-operative ventriculo-peritoneal shunt by comparing two groups (one group-with pre-operative ventriculo-peritoneal shunt and other group-without preoperative ventriculo-peritoneal shunt) in respect to complications, duration of hospital stay and final outcome at 1 month post-operative follow up. This clinical study was carried out at the department of neurosurgery, BSMMU from November 2008 to April 2010 on patients with posterior fossa tumor with hydrocephalus with symptoms and signs of raised intracranial pressure (ICP) who underwent surgery without preoperative ventriculo-peritoneal shunt. A total of 32 patients were included in this study. Patients were divided into two groups, control group (group-A) underwent ventriculoperitoneal shunt prior to tumor surgery and experimental group (group-B) were not treated with ventriculo-peritoneal shunt prior to tumor surgery. Both groups were followed up during hospital stay and after 1 month of tumor resection. Clinical studies include analysis of the following parameters: i) duration of hospital stay, ii) post-operative complications include cerebrospinal fluid leakage, pseudomeningocele, seizure, meningitis, and shunt blockage and, iii) final outcome at 1 month follow up in modified karnofsky performance scale. We also observed whether or not, use of ventriculo-peritoneal shunt to drain cerebrospinal fluid was useful and safe. The mean duration of hospital stay were 95.1±12.6 days with ranged from 70 to 120 days and 71.5±12.6 days ranged from 36 to 88 days in group-A and group-B respectively. The majority of the patients had no complications in both group, which were 12(70.6%) and 9 (60.0%) in group A and group B respectively. Final outcome at 1 month follow up in modified karnofsky performance scale in both groups were similar. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9963 BMJ 2011; 40(1): 43-47